"Why do They Want Others to Suffer the Same Pain They Have Endured?" Weibo Debates about Pain Relief during Childbirth in Neo/Non-Liberal China. Issue 2 (3rd April 2022) - Zou, Wenxue; Wallis, Cara
Abstract: In this article, we examine the cultural and gendered understandings of labor pain and the underlying obstacles that prevent Chinese women from seeking pain relief during labor and exercising their own autonomy. We conducted a critical discourse analysis of 178 posts containing the phrase wutong fenmian (literally "painless labor") on Weibo, a popular Chinese microblogging platform. By situating our analysis in the contemporary context we call "neo/non-liberal China, " where traditional Chinese thought, market socialism, and a therapeutic mode of governance intertwine, we identify four major themes: traditional thinking rooted in Confucianism; health concerns for mother and child; women's empowerment and control of reproduction; and structural issues within China's healthcare system. We argue that Weibo discourses reflect young women's resistance to Chinese traditional gender ideologies and reveal their strong yearning for self-determination and self-care even as their reproductive "choice" is limited by numerous relational and institutional constraints.